ANALISIS KUALITAS JARINGAN INTERNET BERBASIS HSDPA PADA JARINGAN XL DI WILAYAH PADANG UTARA - Kelmizona Saputra; Yasdinul Huda; Ahmaddul Hadi (Universitas Negeri Padang, 2015)
The background of this research is the number of internet users today, and requires a high-speed internet service. This study aims to find out great: delay, packet loss, and throughput. This type of research in this study is descriptive by using statistical analysis. Measurement delay, packet loss, and throughput using Axence NetTools, the results were compared with standard TIPHON. The study was conducted at three different measurement tititk during morning, noon, and night for 5 days. The analysis showed: (1) large delay measurement TP1 = 144.44 ms; TP2 = 134.48 ms; TP3 = 139.99 ms. Based on the very good standard so TIPHON classified service is still feasible to use. (2) Large Packet loss measurement TP1 = 0.77%; TP2 = 0.86%; TP3 = 2.24%. Based on the very good classified TIPHON standard so it is still feasible to use. (3) large throughput measurements TP1 = 0.63%; TP2 = 0.59%; TP3 = 0.57%. Based on the standard TIPHON classified ugly. Keywords : Delay, Packet loss, Throughput, Axence Nettools